Comparative Assessment of Empirical Coke Deposition Models during n-Butanol Dehydration over a Zeolite-Y-Based Cracking Catalyst - Tri Partono Adhi; Azizah Nabilah; Hanief Aulia; Subagjo Subagjo; I Gusti Bagus Ngurah Makertihartha; Melia Laniwati Gunawan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The dehydration of n-butanol to butenes over zeolite-Y is accompanied by coke formation, which progressively deactivates the catalyst and affects reaction kinetics. In this study, dehydration was performed in an isothermal fixed-bed reactor at 400–500 °C using a commercial zeolite-Y composite catalyst. Coke deposition was quantified gravimetrically, while catalyst characterization showed a Si/Al ratio of 6, surface area of 353.9 m².g⁻¹, pore diameter of 57.2 Å, and pore volume of 0.602 cm³.g⁻¹, confirming a mesoporous structure. Coke accumulation data were analyzed using the Voorhies power-law model and analytical expressions derived from the Dumez–Froment empirical model. Model parameters were estimated by fitting experimental coke content data at different temperatures. The Voorhies model showed excellent agreement with experimental data (R² = 0.96–0.98). Among the Dumez–Froment-based expressions, only the logarithmic form accurately described coke deposition, while other forms resulted in poor fits. The results indicate that coke formation is progressively inhibited by accumulated coke, likely due to pore blockage and reduced accessibility of active sites. These findings identify suitable empirical models for predicting coke deposition and catalyst deactivation during n-butanol dehydration over zeolite-Y catalysts. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).